Analysis Of The Calculation Of Income Tax Article 21 - Kurniawan, Fero; Azis, Azolla Degita; Maulani, Denia (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2023)
This research discusses taxation issues related to Income Tax Article 21 (PPh Article 21) at PT. Developing Consulting Management. This report includes an analysis of the calculation of Income Tax Article 21, deposits and tax reporting. The research results show that the calculation of PPh Article 21 carried out by the company is in accordance with applicable tax regulations. However, there was a delay in depositing and reporting PPh Article 21, which resulted in a non-compliance with the Law on General Provisions and Tax Procedures (UU KUP). The impact of this delay is that there are fines which can cause financial losses and damage the company's image. Therefore, it is recommended that companies improve compliance with deposit and reporting deadlines, improve monitoring systems, provide training to staff, and conduct regular internal audits to ensure compliance with tax regulations. By implementing this recommendation, PT. Bina Management Konsultama can minimize the risk of fines, maintain company authority, and ensure better compliance with applicable tax regulations.